Fresh and hardened properties of binary blend sustainable self-compacting concrete (SCC) containing calcined eggshell and silica fume as partial replacement of cement - Mohd Raizamzamani Md Zain,; Oh, Chai Lian; Lee, Siong Wee; Kang, Chen (Penerbit Universiti Kebangsaan Malaysia, 2024)
The current study explored the fresh and hardened properties of sustainable self-compacting concrete (SCC) incorporating calcined eggshell powder (CaESP) and silica fume (SF) as a partial replacement of cement. Waste materials such eggshells, with their high calcium content, have the potential to be used as a cement substitute for SCC. This effort is primarily driven by the restriction of the area of landfills and the desire to reduce greenhouse gas emissions. This study assesses the SCC mixture’s fresh properties, such as workability, passing ability, and segregation resistance, using a multitude of experimental techniques. In addition, the current study also includes an investigation on the hardened properties of the concrete such as compressive and split tensile strengths. SCC cubic specimens with the cross-sectional size of 100 x 100 x 100 mm were tested under compression, and cylindrical specimens with dimensions of 50 mm diameter x 100 mm height were tested under split-tensile test for 7 and 28 days of water curing. The test specimens’ failure behaviour was then examined. The experimental results revealed that the compressive strength of SCC with combined ESP and SF attained its maximum strength at volume fractions of 10% ESP and 0% SF. Considering split-tensile strength has a direct proportional relationship with compressive strength, the split-tensile strength observation was identical to compressive strength, with 10% ESP and 0% SF reaching the maximum strength under split-tensile strength test. The experimental results into the failure mode of SCC specimens showed that higher percentages of CaESP and SF enhance the susceptibility to cracking in SCC specimens, whereas lower percentages of ESP and SF improve crack resistance. The study’s findings have the potential to elevate the use of waste materials in concrete manufacturing, hence reducing environmental impact and supporting sustainable practices in the construction industry.